Arabidopsis NSE4 Proteins Act in Somatic Nuclei and Meiosis to Ensure Plant Viability and Fertility - Zelkowski, Mateusz; Zelkowska, Katarzyna; Conrad, Udo; Hesse, Susann; Lermontova, Inna; Marzec, Marek; Meister, Armin; Houben, Andreas; Schubert, Veit (Frontiers in Plant Science, 2019)
The SMC 5/6 complex together with cohesin and condensin is a member of the structural maintenance of chromosome (SMC) protein family. In non-plant organisms SMC5/6 is engaged in DNA repair, meiotic synapsis, genome organization and stability. In plants, the function of SMC5/6 is still enigmatic. Therefore, we analyzed the crucial δ-kleisin component NSE4 of the SMC5/6 complex in the model plant Arabidopsis thaliana. Two functional conserved Nse4 paralogs (Nse4A and Nse4B) are present in A. thaliana, which may have evolved via gene subfunctionalization. Due to its high expression level, Nse4A seems to be the more essential gene, whereas Nse4B appears to be involved mainly in seed development. The morphological characterization of A. thaliana T-DNA mutants suggests that the NSE4 proteins are essential for plant growth and fertility. Detailed investigations in wild-type and the mutants based on live cell imaging of transgenic GFP lines, fluorescence in situ hybridization (FISH), immunolabelling and super-resolution microscopy suggest that NSE4A acts in several processes during plant development, such as mitosis, meiosis and chromatin organization of differentiated nuclei, and that NSE4A operates in a cycle-dependent manner. Differential response of NSE4A and NSE4B mutants after induced DNA DSBs suggests their involvement in DNA repair processes.